Helper Innate Lymphoid Cells in Allogenic Hematopoietic Stem Cell Transplantation and Graft Versus Host Disease - Quatrini, Linda; Tumino, Nicola; Moretta, Francesca; Besi, Francesca; Vacca, Paola; Moretta, Lorenzo (Frontiers in Immunology, 2020)
Helper Innate Lymphoid Cells (hILCs), including ILC1s, ILC2s and ILC3s, are mainly localized at the mucosal barriers where they play an important role in tissue regeneration and homeostasis through the secretion of specific sets of cytokines. The recent identification of a circulating ILC precursor able to generate all ILC mature subsets in physiological conditions, suggests that “ILC-poiesis” may be important in the context of hematopoietic stem cell transplantation (HSCT). Indeed, in HSCT the conditioning regimen (chemotherapy and radiotherapy) and Graft vs Host Disease (GvHD) may cause severe damages to mucosal tissues. Therefore, it is conceivable that rapid reconstitution of the hILC compartment may be beneficial in HSCT, by promoting mucosal tissue repair/regeneration and providing protection from opportunistic infections. In this review, we will summarize the evidence for a role of hILCs in allogenic HSCT for the treatment of hematological malignancies in all its steps, from the preparative regimen to the immune reconstitution in the recipient. The protective properties of hILCs at the mucosal barrier interfaces make them an attractive target to exploit in future cellular therapies aimed at improving allogenic HSCT outcome.